Organizational change and its relationship to the quality of performance of principals of secondary schools in Al Balqa governorate from their assistants’ point of - Hasouneh, Dr. Osama A. (Opción, 1970)
The study aimed at identifying the relationship between organizational change and the quality of performance of principals of secondary schools in Al Balqa governorate from the view point of their assistants. The descriptive methodology (Correlational survey) was used. A simple random sample of (100) assistant principals from both sexes was chosen during the second semester of the year 2019/2020. The questionnaire was used as a tool to collect data. Theresearcher recommended the need to intensify the training of school principals on the competencies of the leader, especially the change and time management, as they have an impact on the quality of employee performance.